Small-sided games for technical and tactical development in young rink hockey players - Honório, Samuel (2021)
Rink hockey like any other team sport game is necessary to have a mastery of the game object "the ball" and for this it is necessary that athletes do not have a deficient training steps in that process, because it is during their development, that the athlete is in an optimal situation to improve on this aspect of the game. The study objective was to identify which game model allows young athletes to have a greater number of interactions with the ball in rink hockey in the levels of “Under 8” and “Under 10”. Our study sample consisted of 24 games: 8 games in the 3x3 model; 8 games in the 4x4 model and 8 games in the 5x5 model. The 24 matches are equally divided by the levels of Under 8 and Under 10 with a total of 88 children participating. For data collection instrument we used the deferred observation method where we proceeded to a descriptive analysis of the data to find the means, standard deviation and totals of: Shots, Passes, Interceptions and Goals. The Mann-Whitney and Kruskal-Wallis tests were used for comparisons and for correlations, the Spearman's Test was used to verify whether as the playing area available to the player increased, the player's actions increased as well. The 3x3 model obtained a total of 911 actions, the 4x4 model obtained 923 and the 5x5 game model obtained 799 game actions. The 4x4 game model obtained the highest total number of game actions in all levels analysed suggesting that the implementation of this model brings benefits to the athletes.